Neutrophil extracellular traps contribute to immunothrombosis formation via the STING pathway in sepsis-associated lung injury - Shuainan Zhu; Ying Yu; Mengdi Qu; Zhiyun Qiu; Hao Zhang; Changhong Miao; Kefang Guo (Cell Death Discovery, 2023)
Abstract Neutrophil extracellular traps (NETs) are involved in the activation and dysfunction of multiple overlapping and interacting pathways, including the immune response to injury, inflammation, and coagulation, which contribute to the pathogenesis of sepsis-induced acute lung injury (SI-ALI). However, how NETs mediate the relationship between inflammation and coagulation has not been fully clarified. Here, we found that NETs, through stimulator of interferon genes (STING) activation, induced endothelial cell damage with abundant production of tissue factor (TF), which magnified the dysregulation between inflammatory and coagulant responses and resulted in poor prognosis of SI-ALI model mice. Disruption of NETs and inhibition of STING improved the outcomes of septic mice and reduced the inflammatory response and coagulation. Furthermore, Toll-like receptor 2 (TLR2) on the surface of endothelial cells was involved in the interaction between NETs and the STING pathway. Collectively, these findings demonstrate that NETs activate the coagulant cascade in endothelial cells in a STING-dependent manner in the development of SI-ALI.